Hubungan kesiapan belajar dan kesadaran metakognitif dengan scientific reasoning ability peserta didik Sekolah Dasar dalam pembelajaran IPA - Widuri, Ria -; Saputri, Dwi Yuniasih (Didaktika Dwija Indria, 2026)
This study aims to determine the relationship between learning readiness and metacognitive awareness with Scientific Reasoning Ability of fifth grade elementary school students in learning science in Laweyan District, Surakarta. The research was conducted using quantitative methods with a correlational approach. The sample consisted of 100 fifth-grade students selected through cluster random sampling technique. Data on learning readiness and metacognitive awareness of students were collected through questionnaires while Scientific Reasoning Ability data were collected through a description test. The data were then analyzed using the Multiple Correlation test. The results showed that the two variables together had a very high relationship with Scientific Reasoning Ability (r = 0.851; p < 0.001; R-squared=0.725). Based on these results, the conclusion that can be obtained from this study is that learning readiness and metacognitive awareness have a positive relationship and play an important role in supporting students' Scientific Reasoning Ability. Therefore, teachers can imply the results of this study to design learning that not only focuses on cognitive abilities but also strengthens the aspects of learning readiness and metacognitive awareness that play a role in the process of developing scientific reasoning ability.